Quantification of spatiotemporal parameter behavior during walking speed transitions. (9th November 2020) - Rodman, Claire H.; Martin, Anne E.
Abstract: The biomechanics of constant speed walking have been well quantified, but little is known about transitions between walking speeds. Spatiotemporal behavior (step time, length, and speed) has been investigated in starting, stopping, and walking to running transitions, but speed transitions during walking have yet to be investigated. This study quantified the spatiotemporal parameter behavior during walking speed transitions with a range of magnitudes (or differences between pre- and post-transition normalized speeds ranging from 0.03 to 0.13, or approximately 1.18 m/s to 1.58 m/s). 23 healthy adults walked on a treadmill at five different constant speeds for one minute each to establish a baseline. They then performed walking speed transitions, in which they walked on the treadmill as it randomly changed between the five speeds. Linear mixed effect models showed that subjects converged to slightly different post-transition step time and step length averages than established in the constant speed baseline, but the differences are likely too small to be meaningful (on the order of 0.01 s and 0.01 m). When diverging from the pre-transition speed, subjects either diverged in only step time (with step length remaining the same), only step length (with step time remaining the same), or both step time and step length to reach the post-transition speed, with the behavior strongly tied to the magnitude of the speed transition ( p < 0.001 ). Step time often overshot the new value before converging. The number of steps required for each parameter to converge increased with increasing transition magnitude ( p < 0.001 ) and was consistently higher at all magnitudes for speed than step time and length ( p < 0.001 ). In summary, transition magnitude affected the spatiotemporal behavior during walking speed transitions. Further, step time, length, and speed all exhibited slightly different divergence and convergence behavior during transitions.